Penerapan Model Pembelajaran Think Talk Write Dalam Meningkatkan Hasil Belajar Bahasa Inggris Siswa - Arman Arman; Suardi Suardi; Wardiawati Wardiawati (EDUKASI, 2023)
The problem of this study is the teaching method application that seems conventional or traditional, resulting that student learning outcomes in English language learning is low. The problem statement in this research is how the implementation of the Think Talk Write learning model can improve English language learning outcomes for XI grade students at SMK LPP UMI Makassar. The purpose of this study is to determine the effectiveness of applying the Think Talk Write learning model in improving English language learning outcomes for students at SMK LPP UMI Makassar. The type of research is classroom action research conducted in three stages: the thinking stage, the talking stage, and the writing stage. The thinking stage involves students in thinking about topics or questions related to the English language. The talking stage involves students in group discussions or pair discussions to share their thoughts. The writing stage involves students in writing about the topics they have thought about and discussed earlier. The subjects of this research are 20 students from SMK LPP UMI Makassar, consisting of 11 males and 9 females. Data analysis technique uses descriptive analysis method. The results of this research indicate that the application of the Think-Talk-Write learning model can improve students' English language learning achievement through strengthening understanding, improving speaking skills, and developing writing skills. The conclusion of this research is that the application of the Think Talk Write learning model can improve learning outcomes for students at SMK LPP UMI Makassar in the subject of English language.